Pengawasan Hak-Hak Tenaga Kerja: Peran Dinas Penanaman Modal, Transmigrasi dan Tenaga Kerja - Zanzibar Zanzibar; Dicky Armanda (Asia-Pacific Journal of Public Policy, 2019)
The study aims to review the supervision of Labor Rights in the North Aceh District, particularly in the Krueng Keureutoe Dam Development Project, which is under the responsibility of the Office of Investment, Transmigration, and Manpower. This study involved 12 informants who were determined purposively. It was found that the Krueng Keureutoe Dam Development Project accommodated 630 workers using a budget of Rp. 1.7 trillion whose construction was carried out by PT. Hutama Karya, PT. Widya Karya, PT. Berantas, and PT. Perapen Jo. One of these companies, namely PT. Perapen Jo. The company has 138 workers and it has violated the law in fulfilling its labor rights responsibilities, namely the payment of salaries/wages below the Aceh UMP Rp. 2,000,000/month which should have been Rp. 2,717,750/month. Other problems found that the overtime working hours but without payment; no safety equipment such as helmets, shoes, work clothes; no religious holiday allowance (THR), less company recognition on leaving permit; and lacking supplies of medicines. However, this supervision has not been accomplished completely, because there are still numerous violations of legal rules in fulfilling the rights of workers in this project. This study suggests that the government should give a big concern on this case by conducting intensive and continuous monitoring regularly, giving verbal and written warnings, and providing sanctions if required.